Studying the impact of newly identified candidate genetic variants in familial colorectal cancer type X patients for increased familial colorectal cancer susceptibility - Galvão, Mariana (2024)
Colorectal cancer (CRC) is the third most commonly diagnosed type of cancer in the world and the second with the highest mortality rate. Hereditary CRC syndromes, induced by inherited germline mutations in moderate to high penetrance genes, represent only 5% of all hereditary cases, thus emerging the need to investigate novel genetic variants associated with an increased risk of developing CRC, which may have an impact on the clinical management of patients and their families. The Gastroenterology group from UIPM-IPOLFG has previously identified potentially pathogenic germline variants in a specific gene, which is associated with the autophagy process, in families with familial colorectal cancer type X (FCCTX). With the aim of investigating the potential involvement of this gene in CRC etiology, the presence of genetic variants in the studied gene was evaluated in 1282 patients with an increased risk of CRC, who had previously undergone germline genetic diagnosis for hereditary cancer syndromes. A total of 37 unique and rare variants were identified in 47 patients, ten of which were considered as putative damaging variants after in silico analysis. Overall, most variants were predicted to have an impact in the protein structure and none of them were identified in a group of healthy individuals from the Portuguese population. The associations between the identified variants and clinicopathological features found in this study are suggestive of a distinct clinical-molecular CRC entity. Hence, this study emphasizes the relevance of the concerned gene in CRC etiology. Furthermore, expression analysis of the gene under study in samples from individuals with genetic variants in potential regulatory regions and patients with familial CRC was evaluated. Although no relationship has been identified between the presence of the variants and the expression of the gene, the results suggest that its overexpression could be associated with the development of metastatic disease.